Low‐temperature preparation of high‐performance porous ceramics composed of anorthite platelets - Han, Lei; Huang, Liang; Dong, Longhao; Zhang, Haijun; Pei, Yuantao; Li, Faliang; Jia, Quanli; Zhang, Shaowei (Journal of the American Ceramic Society, 2020)
Platelet‐like anorthite based porous ceramics with improved mechanical strength were fabricated via direct gelcasting and firing at 1223‐1473 K using CaCO3, Al(OH)3, and SiO2 powders as the raw materials, along with H3BO3 and melamine sintering/crosslinking agents. Based on density functional theory calculations, H3BO3 promoted the formation of platelet‐like anorthite at a relatively low temperature via covering the {130} facet of anorthite and reducing the corresponding adsorption energy, which led to the preferential growth along the a‐ and b‐axes. The optimal amount of H3BO3 for the anorthite platelet formation was 0.9 wt%. The porous anorthite sample with an original solid content of 22.0 wt%, after firing at 1373 K, contained 71.0% porosity and exhibited a compressive strength as high as 5.7 MPa, which were comparable or even superior to those of porous anorthite ceramics prepared previously at a much higher temperature (1573‐1723 K), indicating that the preparation strategy reported in this paper is feasible in fabricating high‐performance porous anorthite ceramics at a much milder condition. The thermal conductivity of the porous anorthite sample at 1073 K was as low as 0.266 W/(m·K), much lower than that (0.645 W/(m·K)) of the control sample, suggesting that the former could be potentially used for thermal insulation at high temperatures.